CLASSIFICAÇÃO DE TECIDOS DA MAMA A PARTIR DE IMAGENS MAMOGRÁFICAS EM MASSA E NÃO MASSA USANDO ÍNDICE DE DIVERSIDADE DE MCINTOSH E MÁQUINA DE VETORES DE SUPORTE - Carvalho, Péterson Moraes de Sousa (2012)
Breast cancer is the second most common in the world and which more affects women. In recent years, several Computer Aided Detection/Diagnosis Systems has been developed in order to assist health specialists in the detection and diagnosis of cancer, serving as a second opinion. The aim of this paper is to present a methodology for discrimination and classification of regions extracted from mammograms in mass and non-mass. In this study, Digital Database for Screening Mammography (DDSM) is used. To describe the texture of the region of interest is applied McIntosh Diversity Index, commonly used in ecology. The calculation of this index is proposed in four approaches: through the Histogram, through the Gray Level Co-occurrence Matrix, through the Gray Level Run Length Matrix and through the Gray Level Gap Length Matrix. For the classification of regions in mass and non-mass, is used the supervised classificator Support Vector Machine (SVM). The methodology shows promising results for the classification of masses and non-masses, reaching an accuracy of 93,68%.